Efficacy and Safety of Crofelemer for Noninfectious Diarrhea in HIV-Seropositive Individuals (ADVENT Trial): A Randomized, Double-Blind, Placebo-Controlled, Two-Stage Study. Issue 6 (November 2013) - MacArthur, Rodger D.; Hawkins, Trevor N.; Brown, Stephen J.; LaMarca, Anthony; Clay, Patrick G.; Barrett, Andrew C.; Bortey, Enoch; Paterson, Craig; Golden, Pamela L.; Forbes, William P.
Abstract : Background: HIV-associated diarrhea remains a significant concern with limited treatment options.Objective: To determine the optimal dose, efficacy, and safety of crofelemer for noninfectious diarrhea.Methods: This randomized, double-blind, phase 3 trial used a 2-stage design. Both stages included 2-week screening, 4-week placebo-controlled treatment, and 20-week placebo-free (open-label) extension phases. In stage I, 196 HIV-seropositive patients with chronic diarrhea were randomized to crofelemer 125 mg, 250 mg, or 500 mg or placebo twice daily. Using a prospective analysis, the 125-mg twice-daily dose was selected for stage II. In stage II, 180 new patients were randomized to crofelemer 125 mg twice daily or placebo for 4 weeks. Primary efficacy analysis was the percentage of patients (stages I/II combined) who achieved clinical response (defined as ≤2 watery stools/week during ≥2 of 4 weeks). During the placebo-free extension phase, response (≤2 watery stools) was assessed weekly.Results: Significantly more patients receiving crofelemer 125 mg achieved clinical response versus placebo (17.6% vs 8.0%; one-sided, P = .01). Crofelemer 125 mg resulted in a greater change from baseline in number of daily watery bowel movements ( P = .04) and daily stool consistency score ( P = .02) versus placebo. During the placebo-free extension phase, percentages of weekly responders ranged from 40% to 56% at weeks 11 to 24. Crofelemer was minimally absorbed, well tolerated, did not negatively impact clinical immune parameters, and had a safety profile comparable to placebo.Conclusions: In HIV-seropositive patients taking stable antiretroviral therapy, crofelemer provided significant improvement in diarrhea with a favorable safety profile.